Competency or Duty – Methods of Selection in Practice - Gabor Fejes (Communications - Scientific letters of the University of Zilina, 2007)
My work deals with the connection between selection methods and competencies. It seeks an answer how company managers interpret the notion of competency, how important labour selection is according to those competencies. The choice among these methods is determined by conscious or rather subjective aspects, traditions and company culture. The findings are the partial results of a current, practical research. The subject is of a significant importance, as there are hardly any researches dealing with selection and its methods. However, its practical importance is beyond doubt, since the reason for the efficiency of organizations and the only resource of permanent competitive edge is the individual. This fact requires the use of selection methods that provide the satisfaction of employees beyond company efficiency.